Evaluating the Effectiveness of Traffic Sign Violation Law Enforcement in Indonesia: A Normative Analysis - Tarmizi Rambe, Zulpan; Hutasoit, Ispandir; Anugrah Bhakti, Rizki Tri; Afni Maileni, Dwi (Jurnal Cakrawala Hukum, 2025)
Traffic sign violations remain a critical and unresolved public safety challenge in Indonesia, contributing to tens of thousands of fatalities annually and generating economic losses exceeding hundreds of trillions of rupiah. Despite the existence of a comprehensive regulatory framework anchored in Law Number 22 of 2009 on Road Traffic and Transportation and operationalized through the Electronic Traffic Law Enforcement (ETLE) system, enforcement outcomes remain structurally inadequate and behaviorally ineffective. This research employs a normative juridical method utilizing a statute approach and a conceptual approach to conduct a comprehensive evaluation of the law enforcement framework governing traffic sign violations in Indonesia. Applying Soerjono Soekanto's tripartite model of legal effectiveness encompassing legal structure, legal substance, and legal culture the analysis identifies systemic misalignments across all three dimensions: infrastructural undercoverage and inter-agency fragmentation at the structural level; disproportionately low sanctions and evidentiary inadequacy at the substantive level; and rational non-compliance rooted in low enforcement certainty at the cultural level. This research introduces the concept of the integrated enforcement matrix as its primary normative contribution, proposing simultaneous and coordinated reforms across institutional infrastructure, sanction architecture, and legal culture development as the only credible pathway toward closing Indonesia's persistent traffic enforcement gap.